جۆرەکانی ئایدیۆلۆجیا لەڕۆمانی کورديی باشووری کوردستاندا (1975 - 2000) - محمد, عبدالقادر حمەأمین; محمد, میران جلال (Sulaimani Journal for Humanities, 2022)
The novel genre has always been considered one of the widest and most general genres, and it has remained so for a long time. When compared to other genre categories, it is more easily branched and spread. As a result, this quality of being easily transmitted has become a fantastic phenomenon, and it has elevated this genre to the point where it may be explored and coupled with texts and their beings. Ideology, as well as other connected ideological concerns, is phenomena that have arisen as a result of the genre's existence. It has also played an important role in Novel's participation throughout its history, from its inception to the present, with all of its stages of development and evolution. From a historical standpoint, Kurdish Novel arose during a period marked by numerous political occurrences such as battles and revolutions. As a result of these causes having such a large impact on the Kurdish novel, it has become increasingly ideological, to the point where the novel has become more focused on ideology than on other technical parts of the book. It has led readers of that era's novels to believe that they are being heavily guided towards an ideology in a book that has large slogans and other miscellaneous materials. This study aims to examine how various types of ideology have influenced Kurdish novels, particularly those written between 1975 and 2000, because that quarter-century was full of significant events such as revolutions, Nisco (failure), Uprisings, Kurdish massive immigration, as well as other political, social, and humanitarian issues that were directly related to the lives of every Kurdish independent member.